Was bail-out a success? Evidence from the investment-cash flow relationship - Mohd Adib Ismail,; Mansor H. Ibrahim,; Mohd Pisal Zainal,; Mohammed Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The 1997-1998 Asian financial crisis affected the balance sheets of many Malaysian firms, which increased the financial constraints on such firms. To counter the impacts, the Malaysian government carried out various directed policy measures known collectively as the bail-out policy. The present paper examines the success of the policy to reduce the financial constraints. The present paper uses panel estimation methods to analyze the relationship between firms’ investments and their cash flows. The sample of study is split into two subsamples, consisting of the periods before and after the financial crisis, respectively. The success of the policy is measured based upon the easing of financial constraints faced by Malaysian firms. Using annual financial data, consisting of unbalanced panel from the period of 1988 to 2005, the results found favour the bail-out policy. This finding indicates the success of the bail-out policy to reduce the severity of financial constraints.